Analysis of Natural Lighting and Energy Conservation of a University Teaching Building Based on BIM Technology. Issue 1 (July 2020) - Liu, Fei; Xiao, Xiong; Liu, Menglin; Zeng, Huilin; Zhang, Lili
Abstract: This paper first collected the design drawings of the second teaching building of the College of Architecture and Urban-Rural Planning, Sichuan Agricultural University, and used Ecotect Analysis software to conduct 1:1 model of the standard floor of the building. The standard layer light environment is analysed from the aspect of natural lighting. According to the simulation analysis results, the window to ground ratio (independent variable) is raised by layers to increase the area of natural lighting. The overall lighting design of the building before and after optimization was compared, and two Chinese national standards, Standard for Daylighting Design of Buildings and Assessment Standard for Green Building, were used to evaluate the lighting capacity of the building through natural lighting coefficient (dependent variable). The analysis indicates that the building meets the requirements of green design. At the same time, it was found that with the increase of the ratio of window to ground, the average value of the lighting coefficient increased steadily, and the area percentage of the lighting coefficient ≥3.6% also increased, but the increase gradually decreased and tended to be stable.